Exacerbation phenotyping in chronic obstructive pulmonary disease. Issue 5 (28th October 2013) - MacDonald, Martin; Korman, Tony; King, Paul; Hamza, Kais; Bardin, Philip
Abstract : Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are crucial events but causes remain poorly defined. A method to clinically 'phenotype' AECOPD have been proposed, and 52 hospitalized chronic obstructive pulmonary disease exacerbations according to underlying aetiology have now been prospectively phenotyped. Multiple exacerbation phenotypes were identified. A subpopulation coinfected with virus and bacteria had a significantly longer length of hospital stay, and this pilot study indicates that exacerbation phenotyping may be advantageous.